ALEXANDER FAYNBERG - Mirsalikhova Robiya Timurovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
This abstract offers insights into the influential contributions of Alexander Faynberg to the prosperity of Uzbek literature. Exploring the multifaceted impact of Faynberg's work, this abstract highlights his role in reshaping literary discourse, nurturing cultural exchange, and fostering creative innovation within the Uzbek literary landscape. Through an examination of key themes, stylistic influences, and socio- cultural ramifications, this abstract presents a comprehensive overview of the enduring legacy and transformative influence of Alexander Faynberg's contributions to Uzbek literature.